2014
DOI: 10.1016/j.ejcdt.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Serum eosinophilic cationic protein and high sensitive C-reactive protein as alternative parameters for differentiation of severity stages and monitoring control in bronchial asthma patients

Abstract: Background: High sensitive C-reactive protein (hs-CRP) and eosinophilic cationic protein (ECP) have been shown to be associated with asthma in recent studies. However, the relationship between hs-CRP and the control of asthma has not been clearly identified yet.Patients and methods: Thirty patients with newly-diagnosed bronchial asthma and 20 healthy individuals were enrolled in this study. In addition to medical history and physical examination, asthma was assessed according to the Global Initiative for Asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…ICS including fluticasone and budesonide have been shown to be effective in reducing serum levels of hs-CRP [19] and ECP [20] asthma. In line with our findings, previously serum hs-CRP and ECP were reduced in asthmatic patients who were followed up after 2 months of therapy [16]. To our knowledge, our study is the first to compare the effectiveness of different ICS/LABA combinations on serum levels of hs-CRP and ECP and thus further studies are needed.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…ICS including fluticasone and budesonide have been shown to be effective in reducing serum levels of hs-CRP [19] and ECP [20] asthma. In line with our findings, previously serum hs-CRP and ECP were reduced in asthmatic patients who were followed up after 2 months of therapy [16]. To our knowledge, our study is the first to compare the effectiveness of different ICS/LABA combinations on serum levels of hs-CRP and ECP and thus further studies are needed.…”
Section: Discussionsupporting
confidence: 88%
“…Inflammatory markers as hs-CRP and ECP are increased in asthmatics compared to healthy individuals [14], [15], [16]. hs-CRP is an indicator of chronic, low grade inflammation in many conditions including asthma [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study revealed that hsCRP level was significantly elevated in patients with asthma attacks and was related to the state of asthma exacerbation [17]. Sileem et al [18] demonstrated that serum concentrations of hsCRP and tIgE significantly increased in asthmatic patients compared with those in healthy individuals. In our study, 72.8% of allergic patients showed an increase in hsCRP concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The development of airway remodeling may not be solely due to local airway inflammation. Systemic inflammation may be associated with the development of airway remodeling, although the data supporting this connection is still limited (142,143), and there is no clinical study yet in the population with asthma and obesity. Individuals with severe asthma exhibited significantly greater WT% and a higher WA% compared to those with mild-to-moderate asthma and healthy individuals (134).…”
Section: The Intricate Inflammatory Processes Shared Between Asthma A...mentioning
confidence: 99%